2018
DOI: 10.1007/s11356-018-3858-1
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in carbon intensity in EU-28: analysis based on club convergence

Abstract: This study examines the convergence properties of CO2 intensity in EU-28 countries, using panel data for the period 1990 to 2016. We use Phillips and Sul's (2007) approach to test for CO2 intensity convergence and identify convergence clubs. In addition to the EU-28 members, we analyze the EU-15, and the new EU members (EU-new) that joined after 2004, as distinct groups for the periods 1990-2016, 1990-2004, and 2005-2016. Our results show no convergence to a single group among the EU countries during the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Their findings indicated a decreasing trend of carbon intensity in general, yet the decreasing rates for individual countries were divergent to a great extent and most middle-and low-income economies experienced a growing trend of CIs. Emir et al (2019) observed the convergence situation of carbon intensity in EU-28 countries but found that inequity of the performance (i.e., carbon intensity) was significant across the member countries.…”
Section: Cross-country Comparison Of Carbon Emission Performancementioning
confidence: 99%
“…Their findings indicated a decreasing trend of carbon intensity in general, yet the decreasing rates for individual countries were divergent to a great extent and most middle-and low-income economies experienced a growing trend of CIs. Emir et al (2019) observed the convergence situation of carbon intensity in EU-28 countries but found that inequity of the performance (i.e., carbon intensity) was significant across the member countries.…”
Section: Cross-country Comparison Of Carbon Emission Performancementioning
confidence: 99%
“…Another study by [4] shows the existence of the ecological footprint convergence among G20 countries over 1961-2014. We can find convergence properties in CO 2 intensity for EU-28 countries from 1990 to 2016 in the study of [5] isolating five to seven clubs (EU-28), three to five (EU-15 and EU-new). Close, similar results to the one in our study with two different steady states (club convergence) are present in the sample of 77 countries over 1961-2014, as we can see in [7].…”
Section: Discussionmentioning
confidence: 85%
“…Authors demonstrated the convergence in the ecological footprints of G20 countries between 1961 and 2014. Convergence dynamics in CO 2 intensity for the EU-28 countries from 1990 to 2016 in the work of (Emir et al, 2018) [5], are isolated in five to seven clubs (EU-28), three to five (EU-15 and EU-new). Finally, research by (Haider and Akram, 2019) finds that two distinct steady states (club convergence) exist in a sample of 77 nations from 1961 to 2014 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, differences in the usage of alternative energy sources are also linked to differences in fossil fuel endowment. It is therefore unsurprising that despite the existence of convergence evidence in carbon emissions (Emir et al ( 2019 ); Erdogan and Acaravci ( 2019 ); Erdogan and Solarin ( 2021 ); Payne and Apergis ( 2021 ); Solarin ( 2019 ); the outcome of this study is consistent with empirical findings of studies such as Aldy ( 2006 , 2007 ), Criado and Grether ( 2011 ), Herrerias ( 2013 ) Yamazaki et al ( 2014 ), and Li et al ( 2014 ) who have also provided evidence of divergence in carbon emissions.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%